Evaluation of Effect of Herbal Irrigant on Microhardness of Root Dentin: An in vitro Study - Anuya Ravindra Koparde; Anupam Sandeep Sharma; Aniket Jadhav; Aishwarya Handa; Abhijit Bajirao Jadhav; Madhura A. Jadhav (Journal of International Clinical Dental Research Organization)
Introduction: This study evaluated the effect of an herbal irrigant (6.5% grape seed extract [GSE] solution) on the microhardness of root dentin, which is treated with sodium hypochlorite (NaOCl) and ethylenediaminetetraacetic acid (EDTA) (commonly used endodontic irrigants). Proanthocyanidin, a naturally occurring collagen cross-linking agent (found in GSE), was tested for its impact on root dentin. Materials and Methods: A double-ended cutting diamond disc was used to decoronate 8 extracted single-rooted, single-canal premolars. Then, they were divided longitudinally into buccal and lingual segments to create 16 samples, which were implanted in acrylic resin so that each sample’s inner dentin surface was visible. Samples were submerged in 5.25% NaOCl for 2 min, after which they were submerged in 17% EDTA solution for 2 min. The samples were split into two groups at random. Samples from Group 1 were treated with 6.5% GSE solution for 2 min. Samples in Group 2 were submerged in distilled water for 2 min (control group). Vickers microhardness unit was used to test samples for microhardness. The statistical analysis was performed using SPSS software. Unpaired t-test was used to compare groups. Results: Group 1 microhardness score ranged from 79 to 94, whereas Group 2 ranged from 34 to 59. A statistically significant result was obtained between the microhardness in both the groups. Conclusion: The results of the intergroup comparison showed that 6.5% of GSE solution increased the microhardness values of root dentin that had been treated with standard endodontic irrigants.